Clinical predictors of COVID‐19 disease progression and death: Analysis of 214 hospitalised patients from Wuhan, China. (8th November 2020) - Liu, Jie; Liu, Zilong; Jiang, Weipeng; Wang, Jian; Zhu, Mengchan; Song, Juan; Wang, Xiaoyue; Su, Ying; Xiang, Guiling; Ye, Maosong; Li, Jiamin; Zhang, Yong; et al.
Abstract: Introduction: COVID‐19 has spread rapidly worldwide and has been declared a pandemic. Objectives: To delineate clinical features of COVID‐19 patients with different severities and prognoses and clarify the risk factors for disease progression and death at an early stage. Methods: Medical history, laboratory findings, treatment and outcome data from 214 hospitalised patients with COVID‐19 pneumonia admitted to Eastern Campus of Renmin Hospital, Wuhan University in China were collected from 30 January 2020 to 20 February 2020, and risk factors associated with clinical deterioration and death were analysed. The final date of follow‐up was 21 March 2020. Results: Age, comorbidities, higher neutrophil cell counts, lower lymphocyte counts and subsets, impairment of liver, renal, heart, coagulation systems, systematic inflammation and clinical scores at admission were significantly associated with disease severity. Ten (16.1%) moderate and 45 (47.9%) severe patients experienced deterioration after admission, and median time from illness onset to clinical deterioration was 14.7 (IQR 11.3‐18.5) and 14.5 days (IQR 11.8‐20.0), respectively. Multivariate analysis showed increased Hazards Ratio of disease progression associated with older age, lymphocyte count <1.1 × 10⁹/L, blood urea nitrogen (BUN)> 9.5 mmol/L, lactate dehydrogenase >250 U/L and procalcitonin >0.1 ng/mL at admission. These factors were also associated with the risk of death except for BUN. Prediction models in terms of nomogram for clinical deterioration and death were established to illustrate the probability. Conclusions: These findings provide insights for early detection and management of patients at risk of disease progression or even death, especially older patients and those with comorbidities.